Six bufadienolides derivatives are the main active substance against human colorectal cancer HCT116 cells of Huachansu injection - Feng Pan; Keyu Lu; Zeli Chun; Nan Yang; Lingjie Meng; Sanhua Li; Yun Liu (Elsevier, 2024)
Background: Huachansu injection (HCS) is an aqueous extract preparation of Traditional Chinese Medicine (TCM) toad skin (Bufo melanosticus or B. bufo gargarizans). As a national second-class and self-developed TCM preparation, it is widely used to treat human colorectal cancer (CRC), yet its substantial toxic side effects, such as vascular irritation reaction, drug fever, and allergic reactions, pose a considerable challenge during clinical use. In-depth research on the material basis of HCS' traditional efficacy is essential for developing more effective and less toxic medicine. Identifying the main components responsible for the efficacy of HCS is crucial in determining its material basis and explaining any adverse reactions. Purpose: The purpose of this study is to clarify the main active components of HCS as a growth inhibitory agent against CRC HCT116 cells and to further understand the material basis of its anti-CRC properties. Methods: Sulforhodamine B (SRB) assay was used to screen the compound with strong inhibitory activity against HCT116 cells from 44 compounds isolated from aqueous extracts of toad skin (B. melanosticus). The screened compounds as standard and MeOH extracts from HCS were determined by HPLC coupled with triple quadrupole mass spectrometry. The partial MeOH extract was subjected to HPLC system using solvents in a gradient of increasing polarity, yielding 12 fractions in total (HCS1 to HCS12). Besides, the screened active compounds were knocked out from HCS to obtain a fraction as a negative control, and the knocked-out components were collected as one fraction using semi-preparative HPLC. Those fractions were submitted to HPLC-MS/MS or HPLC-DAD system to determine the presence or absence of the screened compounds. In addition, cytotoxicity of those prepared fractions against CRC HCT116 cells was evaluated to determine the effect of the screened compounds in the anti-CRC of HCS. Results: Six compounds, namely arenobufagin, telocinobufagin, gamabufalin, hellebrigenin, 19-hydroxylbufagin and argentinogenin, were screened for their inhibitory activity (with an IC50 value of less than 400 nM), and were present in HCS at a total-mass-percentage of 1.35×10−3 % in HCS MeOH extract. In addition, those 6 compounds were mainly distributed in HCS8, which also showed the strongest inhibitory activity against HCT116 cells. And the results of multicomponent knockout assay indicated the negative control lost its anti-CRC activity significantly, while the activity can be restored after those 6 compounds were added to the negative control. Conclusions: Those six bufadienolides derivatives are responsible for the anti-CRC HCT116 cells activity of HCS, and are the main components of HCS on anti-CRC. Through this research, we can more clearly understand the main anti-CRC active components in HCS, and the work also lays the foundation for the development of more effective and less toxic medicine from HCS.